Effect of a Bacillus subtilis strain on flax protection against Fusarium oxysporum and its impact on the root and stem cell walls. (1st October 2020) - Planchon, Aline; Durambur, Gaëlle; Besnier, Jean‐Baptiste; Plasson, Carole; Gügi, Bruno; Bernard, Sophie; Mérieau, Annabelle; Trouvé, Jean‐Paul; Dubois, Caroline; Laval, Karine; Driouich, Azeddine; Mollet, Jean‐Claude; et al.
Abstract: In Normandy, flax is a plant of important economic interest because of its fibres. Fusarium oxysporum, a telluric fungus, is responsible for the major losses in crop yield and fibre quality. Several methods are currently used to limit the use of phytochemicals on crops. One of them is the use of plant growth promoting rhizobacteria (PGPR) occurring naturally in the rhizosphere. PGPR are known to act as local antagonists to soil‐borne pathogens and to enhance plant resistance by eliciting the induced systemic resistance (ISR). In this study, we first investigated the cell wall modifications occurring in roots and stems after inoculation with the fungus in two flax varieties. First, we showed that both varieties displayed different cell wall organization and that rapid modifications occurred in roots and stems after inoculation. Then, we demonstrated the efficiency of a Bacillus subtilis strain to limit Fusarium wilt on both varieties with a better efficiency for one of them. Finally, thermo‐gravimetry was used to highlight that B. subtilis induced modifications of the stem properties, supporting a reinforcement of the cell walls. Our findings suggest that the efficiency and the mode of action of the PGPR B. subtilis is likely to be flax variety dependent. Abstract : Bacillus subtilis strain ATCC 6633 is able to limit the wilt symptoms caused by the pathogenic fungus Fusarium oxysporum f. sp. lini on two Linum usitatissimum (flax) varieties, Aramis and Mélina and to induce modifications of the cell wall composition and stem thermal stability properties, suggesting a cell wall reinforcement.